2008
DOI: 10.1186/1476-511x-7-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of endothelial nitric oxide synthase promoter region (T-786C) gene polymorphism with acute coronary syndrome and coronary heart disease

Abstract: Background: Nitric oxide (NO) is an endothelium derived relaxing factor (EDRF) which has an important role for regulating the heart-vessel physiology. The objective of this study was to evaluate the effects of the eNOS T-786C polymorphism on lipid parameters and the development of acute coronary syndrome (ACS) and coronary heart disease (CHD) for the first time in a Turkish study group. We have analyzed the genotype frequencies of the T-786C polymorphism of the eNOS gene in 10 ACS patients (5 men, 5 women), 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 32 publications
1
15
0
1
Order By: Relevance
“…TT was the genotype most frequently observed in both patients with CAD (Ciftçi et al, 2008). Similarly, Dosenko et al (2005) studying a group of patients with ACS in the Ukrainian population, found the C polymorphism of the 5'-flanking region of the eNOS gene 2.7-fold more frequently in patients with ACS than in controls.…”
Section: Discussionmentioning
confidence: 98%
“…TT was the genotype most frequently observed in both patients with CAD (Ciftçi et al, 2008). Similarly, Dosenko et al (2005) studying a group of patients with ACS in the Ukrainian population, found the C polymorphism of the 5'-flanking region of the eNOS gene 2.7-fold more frequently in patients with ACS than in controls.…”
Section: Discussionmentioning
confidence: 98%
“…It was demonstrated in previous studies that the T/C (-786) eNOS polymorphism is associated with diabetic nephropathy and end stage renal disease [16,36], diabetic retinopathy and diabetic macula edema [38,39], albuminuria [40], rheumatoid arthritis [41], acute coronary syndrome [42,43], coronary artery disease [44] essential and arterial hypertension [45,46], inflammation and atherosclerosis [37,47]. In our study, significant results appeared for the T/C eNOS polymorphism in the comparison with genotype's frequencies between the healthy individuals and the groups (DM, DN, NDRD respectively) of diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Гіпотеза щодо впливу поліморфізму Т-786С промотора гена еNOs на перебіг і прогноз ІХС підтверджується резуль-татами досліджень китайської та європейської популяції, в яких доведено зв'язок СС генотипу з розвитком ІМ [11,12].…”
Section: таблиця 2 частоти алелів і генотипів I/d поліморфізму гена аunclassified